The design and pilot evaluation of an interactive learning environment for introductory programming influenced by cognitive load theory and constructivism - Moons, Jan; De Backer, Carlos (Computers and education, 2013)
This article presents the architecture and evaluation of a novel environment for programming education. The design of this programming environment, and the way it is used in class, is based on the findings of constructivist and cognitivist learning paradigms. The environment is evaluated based on qualitative student and teacher evaluations and experiments performed over a three year timespan. As the findings show, the students and teachers see the environment and the way it is used as an invaluable part of their education, and the experiments show that the environment can help with understanding programming concepts that most students consider very difficult. ► We propose a set of guidelines based on learning theory for designing program visualization software. ► We present the architecture and design of a novel program visualization application. ► We report on the positive results of a qualitative and quantitative study using the visualization environment.